ANALISIS CUSTOMER CONTACT DAN SERVICE GUARANTEE TERHADAP CUSTOMER SATISFACTION DENGAN CUSTOMER VALUE SEBAGAI VARIABEL INTERVENING - Fahmi Haikal Maladzi; Rizal Hari Magnadi (JURNAL STUDI MANAJEMEN ORGANISASI, 2015)
The background of this research is the reduction of direct interaction and a guaranteethat the company gave notice to the customer. This study aims to determine how muchinfluence customer contact and service guarantee to customer satisfaction with customervalue as an intervening variable in train service users operating area 4 Semarang.The number of samples in thie study are 100 respondents train service users ho wereselected based on purposive sampling method. The questionnaire is distribute in April2015. The data obtained are processed using validity and reliability test, classicassumption test, multiple regression analysis, goodness of fit test with regressioncoefficients, test F and test T.The result of this study showed that the variables of customer contact provide value43,6% and service guarantee provide value 42,7% which both have a positive andsignificant impact on customer value. Then customer contact provide value 25,8% andcustomer value with a value of 62,7% which both have a positive and significant impacton customer satisfaction, while service guarantee with a value of 1,4% have a positiveeffect but not significant on customer satisfaction.Keywords : customer contact, service guarantee, customer value, customer satisfaction.